The Influence of the PBL Model on Students' Critical Thinking Skills in Science Learning - Ismail, Meyke; Payu, Citron S.; Supartin; Paramata, Dewi Diana; Uloli, Ritin; Odja, Abdul Haris (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
This research aims to determine the influence of the Problem-Based Learning (PBL) Model on students' Critical Thinking Skills in science learning at SMP Negeri 4 Gorontalo. This research method is experimental, with a pretest-posttest control group design. The population in this study was class VII at SMP Negeri 4 Gorontalo for the 2024/2025 academic year. The sample consists of 2 classes, namely the experimental and control classes, using the Simple Random Sampling technique. Data collection uses a critical thinking skills test in the form of an essay consisting of 10 questions. Data collection techniques use normality tests, homogeneity tests, N-Gain tests, and hypothesis tests. The Independent Sample T-Test Hypothesis Test data shows that t-count > t-table means that H1 is accepted and the PBL Model influences students' Critical Thinking Skills in science learning.